2013
DOI: 10.1111/apt.12571
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: highly selective 5‐HT4 agonists (prucalopride, velusetrag or naronapride) in chronic constipation

Abstract: Summary Background Highly selective 5‐HT4 agonists have been suggested for the treatment of chronic constipation (CC). Aim To assess the effects of highly selective 5‐HT4 agonists (prucalopride, velusetrag or naronapride) on patient‐important clinical efficacy outcomes and safety in adults with CC. Methods We searched the medical literature in January 2013 using MEDLINE/Pubmed, Embase, Cochrane Library, and Web of Science/Scopus for randomised, controlled trials of highly selective 5‐HT4 agonists in adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 35 publications
7
81
0
2
Order By: Relevance
“…However, there are several systematic reviews and meta-analyses evaluating the role of prucalopride [59][60][61][62][63][64][65][66][67][68] in the management of chronic constipation and their findings are consistent with the findings of the current study. Although the scope of the current article is the evaluation of clinical effectiveness and adverse events related to prucalopride only, previously reported systematic reviews [59][60][61][62][63][64][65][66][67][68] have reported its safety, efficacy, pharmacokinetics, and tolerability providing supporting evidence to our conclusions. As reported by Tack et al 69 "Prucalopride is an important addition to the therapeutic abilities for treating chronic constipation, especially in females poorly responding to laxatives.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, there are several systematic reviews and meta-analyses evaluating the role of prucalopride [59][60][61][62][63][64][65][66][67][68] in the management of chronic constipation and their findings are consistent with the findings of the current study. Although the scope of the current article is the evaluation of clinical effectiveness and adverse events related to prucalopride only, previously reported systematic reviews [59][60][61][62][63][64][65][66][67][68] have reported its safety, efficacy, pharmacokinetics, and tolerability providing supporting evidence to our conclusions. As reported by Tack et al 69 "Prucalopride is an important addition to the therapeutic abilities for treating chronic constipation, especially in females poorly responding to laxatives.…”
Section: Discussionsupporting
confidence: 89%
“…[59][60][61][62][63][64][65][66][67] However, this study provides up to date, comprehensive and cumulative evidence on the use of prucalopride that meaningfully reduce symptoms related to chronic constipation. One review 59 reported the combined analysis of 3 trials, 4 reviews 62,64,65,67 reported the combined analysis of 4 trials each, 2 reviews 64,66 reported systematic review of the trials evaluating four 5-HT 4 agonist agents, whereas 3 reviews 60,61,68 were evidence reviews.…”
Section: Discussionmentioning
confidence: 99%
“…70,71 Prucalopride, a 5-HT 4 receptor agonist, is effective and well-tolerated for treatment of chronic constipation at a dose of 2 mg/day for adults and 1 mg/day for those over 65 years of age. 72 These new drugs have not been assessed in dyssynergic defecation.…”
Section: New Drugs For Constipationmentioning
confidence: 99%
“…It is expressed in enteric neurons and smooth-muscle cells. Activation of 5-HT4 receptors are located on myenteric with cholinergic motor neurons which stimulate gut motility through enhanced release of acetylcholine (Shin et al, 2014). 5-HT4 receptors are also found in the central nervous system (CNS), where their functions remain largely unclear.…”
Section: -Ht4 and 5-ht5 Receptorsmentioning
confidence: 99%